2012
DOI: 10.1590/s0101-20612012005000047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whey protein concentrate on texture of fat-free desserts: sensory and instrumental measurements

Abstract: It is important to understand how changes in the product formulation can modify its characteristics. Thus, the objective of this study was to investigate the effect of whey protein concentrate (WPC) on the texture of fat-free dairy desserts. The correlation between instrumental and sensory measurements was also investigated. Four formulations were prepared with different WPC concentrations (0, 1.5, 3.0, and 4.5 wt. (%)) and were evaluated using the texture profile analysis (TPA) and rheology. Thickness was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
0
17
0
3
Order By: Relevance
“…The sucralose chocolate dairy dessert presented the lowest value of elasticity differing statistically ( P ≤ 0.05) from the others. Vidigal and others () reported that fat‐free desserts supplemented with whey protein concentrate showed greater elasticity.…”
Section: Resultsmentioning
confidence: 99%
“…The sucralose chocolate dairy dessert presented the lowest value of elasticity differing statistically ( P ≤ 0.05) from the others. Vidigal and others () reported that fat‐free desserts supplemented with whey protein concentrate showed greater elasticity.…”
Section: Resultsmentioning
confidence: 99%
“…The firmness (in g force) was automatically recorded (12 measurements per loaf) by the data processing software on days 1, 3 and 7 after baking according to the AIB standard procedure. Three batches of each composition were prepared, and at least five measurements were performed on each batch (Vidigal et al, 2012). (appearance, colour, odour, flavour, texture by touch and mouthfeel, cohesiveness and global appreciation) Sensory evaluation of the broa samples was conducted 24 h after their production using a hedonic quantitative response scale (International Drganization for Standardization, 2003) in a test room (International Drganization for Standardization, 2007) with a consumer panel of 52 assessors.…”
Section: Physical Analysis (Colour and Texture)mentioning
confidence: 99%
“…Whey Protein Concentrate (WPC) has been considered an interesting fat-substitute ingredient due to its functional and technological properties, as well as its nutritional properties since it contains high concentrations of bioactive proteins (Vidigal et al, 2012). Whey protein functionality is associated with its composition and degree of denaturation (Lizarraga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%